Awareness of Abdominal Adiposity as a Cardiometabolic Risk Factor (The 5A Study): Mexico - Garcia-Rubi E (Dove Medical Press, 2011)
Daniel Cuevas Ramos1, Roopa Mehta1, Julieta De La Luz Castro2, Rutila Castañeda Limones3, Ernesto García Rubí4, Carlos A Aguilar-Salinas11Department of Endocrinology, Instituto Nacional de Ciencias Medicas y Nutricion "Salvador Zubiran" (INCMNSZ); 2Cardiodiabetes Unit, Sanofi-Aventis de México; 3Clinical Epidemiology Research Unit, Hospital General Regional No 1 Dr Carlos Mac Gregor Sánchez Navarro; 4Department of Endocrinology, Hospital Angeles Metropolitano, Mexico City, MexicoBackground: The Awareness of Abdominal Adiposity as a Cardiometabolic Risk Factor Study assesses the prevalence of cardiometabolic risk factors in adults with abdominal obesity (waist circumference ≥90 cm in men and ≥80 cm in women) and evaluates how physicians manage these patients.Methods: This is an observational cross-sectional study. Internists, cardiologists, and endocrinologists contributed patients to the study. A standardized questionnaire was completed and registered demographics, anthropometric measurements, lab results from the medical files, and any treatment utilized to manage dyslipidemia, arterial hypertension, diabetes, and cardiovascular disease.Results: A total of 1312 patients was included. The mean age was 49.3 ± 14.6 years and 834 (63.6%) were female. The primary reason for the physician consultation was treatment of obesity (47.5%), followed by management of arterial hypertension (27.7%), diabetes (18.3%), dyslipidemia (14.2%), and cardiovascular disease (7.1%). The majority of patients identified excess body weight as a health problem (81.4%). However, patients had lost a mean of 4.3 ± 3.5 kg. Only 63.4% of patients with arterial hypertension were on drug therapy. Few of them had reached target values for diastolic (24.1%) and systolic/diastolic (13.3%) pressure. Less than half of the patients with dyslipidemia were receiving lipid-lowering medication. Only 32.2% were at their target low-density lipoprotein cholesterol levels. In patients with type 2 diabetes, mean fasting plasma glucose level (8.9 ± 3.4 mmol/L) was above the threshold recommended by current guidelines.Conclusions: The study describes the medical care given to individuals with abdominal obesity during daily clinical practice by general practitioners, cardiologists, and endocrinologists in urban Mexico. Our data confirm that a large proportion of patients are undertreated. Only a small percentage of patients with obesity-related comorbidities reach treatment targets. Interventions proven to be effective in the prevention of chronic complications have in general not been implemented.Keywords: abdominal obesity, waist circumference, dyslipidemia, type 2 diabetes, pattern of care